Long-Term Effect of Pravastatin on Carotid Intima–Media Complex Thickness: The J-STARS Echo Study (Japan Statin Treatment Against Recurrent Stroke). Issue 1 (January 2018) - Koga, Masatoshi; Toyoda, Kazunori; Minematsu, Kazuo; Yasaka, Masahiro; Nagai, Yoji; Aoki, Shiro; Nezu, Tomohisa; Hosomi, Naohisa; Kagimura, Tatsuo; Origasa, Hideki; Kamiyama, Kenji; Suzuki, Rieko; et al.
Abstract : Background and Purpose—: The effect of statins on progression of carotid intima–media complex thickness (IMT) has been shown exclusively in nonstroke Western patients. This study aimed to determine the effect of low-dose pravastatin on carotid IMT in Japanese patients with noncardioembolic ischemic stroke. Methods—: This is a substudy of the J-STARS trial (Japan Statin Treatment Against Recurrent Stroke), a multicenter, randomized, open-label, parallel-group trial to examine whether pravastatin reduces stroke recurrence. Patients were randomized to receive pravastatin (10 mg daily, usual dose in Japan; pravastatin group) or not to receive any statins (control group). The primary outcome was IMT change of the common carotid artery for a 5-year observation period. IMT change was compared using mixed-effects models for repeated measures. Results—: Of 864 patients registered in this substudy, 71 without baseline ultrasonography were excluded, and 388 were randomly assigned to the pravastatin group and 405 to the control group. Baseline characteristics were not significantly different, except National Institutes of Health Stroke Scale scores (median, 0 [interquartile range, 0–2] versus 1 [interquartile range, 0–2]; P =0.019) between the 2 groups. Baseline IMT (mean±SD) was 0.887±0.155 mm in the pravastatin group and 0.887±0.152 mm in the control group ( P =0.99). The annual change in the IMT at 5-year visit was significantly reduced in the pravastatin group as compared with that in the control group (0.021±0.116 versus 0.040±0.118 mm; P =0.010). Conclusions—: The usual Japanese dose of pravastatin significantly reduced the progression of carotid IMT at 5 years in patients with noncardioembolic stroke. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00361530. Abstract : Supplemental Digital Content is available in the text.